2022
DOI: 10.4244/eij-d-22-00246
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous treatment options for acute pulmonary embolism: a clinical consensus statement by the ESC Working Group on Pulmonary Circulation and Right Ventricular Function and the European Association of Percutaneous Cardiovascular Interventions

Abstract: There is a growing clinical and scientific interest in catheter-directed therapy (CDT) of acute pulmonary embolism (PE). Currently, CDT should be considered for patients with high-risk PE, in whom thrombolysis is contraindicated or has failed. Also, CDT is a treatment option for initially stable patients in whom anticoagulant treatment fails, i.e., those who experience haemodynamic deterioration despite adequately dosed anticoagulation. However, the definition of treatment failure (primary reperfusion therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 62 publications
0
91
0
Order By: Relevance
“…Actually, percutaneous catheter-directed treatment is recommended only in high-risk patients in whom thrombolysis is contraindicated or has failed and surgical embolectomy is not available (IIa class of recommendation) and in intermediate-risk patients with hemodynamic deterioration, because its benefits over medical or surgical therapy are still unclear. However, a clinical consensus statement by the ESC Working Group on pulmonary circulation and right ventricular function and the European Association of Percutaneous Cardiovascular Interventions has just been published and it proposed algorithm and timelines of catheter-directed therapies, demonstrating a growing clinical and scientific interest in this novel field ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, percutaneous catheter-directed treatment is recommended only in high-risk patients in whom thrombolysis is contraindicated or has failed and surgical embolectomy is not available (IIa class of recommendation) and in intermediate-risk patients with hemodynamic deterioration, because its benefits over medical or surgical therapy are still unclear. However, a clinical consensus statement by the ESC Working Group on pulmonary circulation and right ventricular function and the European Association of Percutaneous Cardiovascular Interventions has just been published and it proposed algorithm and timelines of catheter-directed therapies, demonstrating a growing clinical and scientific interest in this novel field ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…We reported an early experience, in an Italian tertiary centre, of a high-risk patient treated with Inari Flow system, resulting in a fast improvement of vital signs and instant resolution of patient’ symptoms, without complications. Results of nine randomized clinical trials ( 8 ) are expected to demonstrate the superiority of percutaneous device treatments of PE over medical therapy, but based on our experience, percutaneous mechanical thrombectomy is an effective and safe alternative treatment for patients with PE at high and intermediate risk.…”
Section: Discussionmentioning
confidence: 99%
“…The RoPE Score of our patient was 7 points, indicating a 72% chance that stroke was due to PFO. 16 The analysis of three important PFO trials demonstrated that patients with a RoPE Score ≥7 benefit from a higher-risk reduction of recurrent strokes when undergoing PFO closure than medical therapy alone. 17 In addition, the large size of the PFO, with more than 20 bubbles crossing, is associated with a causal role.…”
Section: Discussionmentioning
confidence: 99%
“…However, this consideration is classified as weak with a low level of evidence 87 . In 2022, the ESC Working Group on Pulmonary Circulation and Right Ventricular Function and the European Association of Percutaneous Cardiovascular Interventions published a consensus paper in which the authors emphasize that, although no robust data exist, there is a potential role for interventional therapies as an alternative reperfusion strategy at specialized centres 105 . Against this background and given the growing scientific and clinical interest in interventional therapies for PE, we summarize the available devices (Table 3 ) and discuss the published evidence and ongoing studies.…”
Section: Interventional Therapiesmentioning
confidence: 99%